Joint mobility/muscular chain elasticity in a cohort of 9- to 11-year school children exposed to a specifically designed professionally guided training - Volta, E.; Canali, V.; Gobbi, G.; Martini, S.; Albanese, C.; Vaccarezza, Mauro; Vitale, M.; Mirandola, P.; Galli, D. (2016)
Purpose: Joint mobility is a fundamental part in physical activity program for children, but a scientific characterization of the methods to improve the articular mobility in healthy children is still poor. The aim of this study was to investigate whether joint mobility/muscular elasticity were related to a merely active lifestyle or could be significantly improved in the presence of a collective, easy-to-perform, but specifically designed and professionally guided program. Methods: Specific functional and anthropometric parameters were single-blind tested on 277 children (aged 9–11 years). 148 were randomly assigned to a physical education program specifically designed to increase elasticity and supervised by professionals (treated group), while 129 (control group) continued their usual physical activity at school, with no specific program. Results: Specific tests were performed and showed a significant improvement of joint mobility compared to non-specific physical activity in 9- to 11-year children. As a secondary end-point, this program was effective also in children of overweight/obese BMI category. Conclusions: These results, building on those from this and other groups, should orientate decision-makers in the area of physical exercise for primary school children towards specifically designed programs based on demographic and anthropometric data.